Pengaruh Berat Badan Lahir Rendah dengan Kejadian Stunting pada Anak Usia 12-23 Bulan di Wilayah Kerja Puskesmas Lubuk Buaya Padang Tahun 2019 - Linda Wati; Monarisa Monarisa; Meta Rikandi (Universitas Batanghari Jambi, 2019)
Stunting (short) is a common nutritional problem faced in Indonesia. The stunting prevalence based on the National Health Survey in 2013 was recorded at 37.2% of all children under five, while in West Sumatra it was recorded at 39.2% of all children under five. In 2018 the national stunting rate was recorded at 30.8% of all toddlers and West Sumatra's figure was 30.0% of all toddlers. This study aims to determine the effect of low birth weight with the incidence of stunting in children aged 12-23 months in the Work Area of Lubuk Buaya Public Health Center in Padang in 2019. The sample in this study amounted to 294 toddlers both with stunting and not stunting. Analysis of the data used is univariate and bivariate, and multivariate. The results showed there was no significant relationship between body weight with the incidence of stunting, there was a significant relationship between the history of infection with the incidence of stunting, there was no significant relationship between breastfeeding and the incidence of stunting, there was no significant relationship between parenting with the incidence of stunting, the most influencing factor for the incidence of stunting in children under five in the Work Area of the Lubuk Buaya Public Health Center in 2019 was parenting with a p value = 0.002. The importance of the Lubuk Buaya Public Health Center in Padang is not only focused on the target, but also on families, especially about mothers and children under five.